Mid-T heat treatments on BCP’ed coaxial cavities at TRIUMF - Kolb, P.; Yao, Z.; Blackburn, A.; Gregory, R.; Hedji, D.; McMullin, M.; Junginger, T.; Laxdal, R. E. (Frontiers in Electronic Materials, 2023)
Mid-T heat treatments in the range from 250 to 400 • C on superconducting radio-frequency (SRF) cavities have been shown to provide high quality factors that rise with applied rf field strength in high frequency, electro-polished (EP), elliptical cavities operating at 2 K, similar to nitrogen doped cavities. The rise in quality factor is attributed to a decrease in the temperature dependent part of the surface resistance R BCS . Until now, no results have been reported for these new treatments on quarter-wave resonators (QWR) and half-wave resonators (HWR). The TRIUMF multi-mode coaxial cavities are dedicated test cavities that allow frequency and temperature resolved performance characterization of treatments without changing environments, therefore providing an excellent test vehicle to test these new treatments with rf frequencies ranging from 200 to 1200 MHz.In this paper, performance measurements from both QWR and HWR cavities are reported and their performance compared with four different treatments: baseline, a conventional 120 • C low temperature bake for 48 hours, and two mid-T bakes at 300 and 400 • C for 3 hours. In addition, sample analysis using SEM, EDX and SIMS of witness samples is also shown.It is found that the mid-T bakes are not directly transferable to low frequency cavities. In the fundamental modes of the two test cavities, no performance gain over the baseline treatment nor a decreasing temperature dependent component with rising rf amplitude was observed. At frequencies above 1 GHz and low temperatures, the mid-T bakes show a reduced field dependence of R BCS compared to both the baseline and 120 • C treatments.